The The Implications of Transformational and Transactional Leadership on Organizational Commitment - Asrarudin (IJHCM (International Journal of Human Capital Management), 2022)
Abstract This research is a literature review that examines various literatures on the implication transformational and transactional leadership. The purpose of this research is to find out the implications of transformational and transactional leadership on organizational commitment; similarities and differences behaviors of transformational and transactional leadership towards organizational commitment. The method used in this research is integrative literature review which assesses, criticizes, and synthesizes different literatures to create new theoretical framework. This research finding shows that transformational and transactional leadership have implications on the commitment of each employee to the values ​​and goals of the organization. Transformational leadership builds long-term relationship while transactional leadership builds short-term relationships with subordinates based on shared goals and rewards are given when subordinates are able to achieve goals and vice versa sanctions are given if the goals cannot be achieved. Creative and innovative behavior is not the main thing but status quo is important.